2013
DOI: 10.1186/1297-9686-45-11
|View full text |Cite
|
Sign up to set email alerts
|

Genomic selection of purebred animals for crossbred performance in the presence of dominant gene action

Abstract: BackgroundGenomic selection is an appealing method to select purebreds for crossbred performance. In the case of crossbred records, single nucleotide polymorphism (SNP) effects can be estimated using an additive model or a breed-specific allele model. In most studies, additive gene action is assumed. However, dominance is the likely genetic basis of heterosis. Advantages of incorporating dominance in genomic selection were investigated in a two-way crossbreeding program for a trait with different magnitudes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
81
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(87 citation statements)
references
References 22 publications
5
81
1
Order By: Relevance
“…In the current study, we also observed similar results, and dominance variation accounted for a small proportion of the total genetic variation (4 to 10%). The lack of change in predictive ability also indicated the difficulty of distinguishing dominance genetic effects from additive genetic effects [9], but it confirmed a previous simulation study that concluded that the use of a dominance model did not negatively affect genomic evaluation even if the trait was purely additive [18]. …”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…In the current study, we also observed similar results, and dominance variation accounted for a small proportion of the total genetic variation (4 to 10%). The lack of change in predictive ability also indicated the difficulty of distinguishing dominance genetic effects from additive genetic effects [9], but it confirmed a previous simulation study that concluded that the use of a dominance model did not negatively affect genomic evaluation even if the trait was purely additive [18]. …”
Section: Discussionsupporting
confidence: 68%
“…However, our results showed that inclusion of dominance deviations did not increase the predictive ability for crossbreds. This result was in line with conclusions in [9, 12, 20], but was opposite to those in [18, 19, 48, 49]. Theoretically, estimating dominance genetic effects should be useful because ignoring them will result in less accurate estimates of allele substitution effects and consequently less accurate estimated breeding values in genomic prediction [11].…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Further, GS with a dominance model was superior for the selection of purebreds for cross‐bred performance (Zeng et al . ). However, few studies have assessed the effect of dominance effects on the accuracy of GEBV in poultry.…”
Section: Introductionmentioning
confidence: 97%
“…Hybrids are then transferred to commercial operations where the final product, usually a three-way cross, is produced by more than one million commercial sows. For such systems, the breeding goal in purebred populations should be optimizing the performance of crossbred progeny [16]. Another important parameter to be evaluated is the genetic diversity of a population, as this is relevant to the sustainable use of genetic resources and continued long-term genetic improvement [17].…”
Section: Introductionmentioning
confidence: 99%